2020
DOI: 10.1108/bij-05-2019-0213
|View full text |Cite
|
Sign up to set email alerts
|

Workplace incivility and knowledge hiding: a research agenda

Abstract: PurposeContemporary organizations report a sharp increase in the incidences of workplace incivility. The purpose of this paper is to capture the impact of workplace incivility on the victimized employee's knowledge-hiding behaviours. The paper proposes that the victim will hide knowledge by playing dumb, evasive hiding and rationalized hiding behaviour.Design/methodology/approachThe paper first focusses on a review of literature on workplace incivility and summarizes the findings through a conceptual review mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 93 publications
4
86
0
3
Order By: Relevance
“…performance, job satisfaction and disengagement) and nonwork outcomes (e.g. stress, emotional exhaustion and work-life imbalance) (Irum et al, 2020 for a review). For example, studies have shown that experiencing interpersonal mistreatment (incivility) in the workplace can induce negative emotions in individuals (Porath and Pearson, 2012).…”
Section: Incivility Reactionsmentioning
confidence: 99%
“…performance, job satisfaction and disengagement) and nonwork outcomes (e.g. stress, emotional exhaustion and work-life imbalance) (Irum et al, 2020 for a review). For example, studies have shown that experiencing interpersonal mistreatment (incivility) in the workplace can induce negative emotions in individuals (Porath and Pearson, 2012).…”
Section: Incivility Reactionsmentioning
confidence: 99%
“…Although there is a rich literature examining the antecedents and responses of workplace incivility, research has not yet studied the underlining mechanisms enticing employees to engage in counterproductive behaviors as a response to workplace mistreatment (Irum et al, 2020). Irum et al (2020) used affective events theory to show how perceived incivility arouses negative emotions in the victims, which in turn push them to respond by hiding knowledge.…”
Section: Incivility and Knowledge Hidingmentioning
confidence: 99%
“…Although there is a rich literature examining the antecedents and responses of workplace incivility, research has not yet studied the underlining mechanisms enticing employees to engage in counterproductive behaviors as a response to workplace mistreatment (Irum et al, 2020). Irum et al (2020) used affective events theory to show how perceived incivility arouses negative emotions in the victims, which in turn push them to respond by hiding knowledge. The findings (Irum et al, 2020) also showed that these relations vary based on gender and other individual factors, and so, the authors concluded that there should be other explanatory variables that need to be explored to better explain why and when perceived incivility leads to knowledge hiding.…”
Section: Incivility and Knowledge Hidingmentioning
confidence: 99%
See 1 more Smart Citation
“…These behaviors are commonly referred to as workplace incivility (Andersson and Pearson, 1999), a phenomenon that exists in all industries and is increasingly common in the workplace (Porath and Pearson, 2010; Porath et al , 2015), affecting both employees and the organization (Schilpzand et al , 2016). Despite the fact that the behavioral manifestations of workplace incivility are of low intensity (Andersson and Pearson, 1999), they can still lead to serious harmful effects (for a review, see Cortina et al , 2017; Irum et al , 2020; Schilpzand et al , 2016). This is perhaps why workplace incivility has received growing attention from organizational researchers over a short span of time (Shin and Hur, 2020).…”
Section: Introductionmentioning
confidence: 99%